Correction: Global injury morbidity and mortality from 1990 to 2017 : results from the Global Burden of Disease Study 2017 - James, Spencer L.; Bärnighausen, Till; Jonas, Jost B.; Moazen, Babak; Mohammed, Shafiu; Panda-Jonas, Songhomitra (Injury prevention, 2020)
James SL, Castle CD, Dingels ZV, et al . Global injury morbidity and mortality from 1990 to 2017: results from the Global Burden of Disease Study 2017. Inj Prev . …